2018
DOI: 10.1111/evo.13433
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic integration of the cervical vertebrae in the Hominoidea (Primates)

Abstract: Phenotypic integration and modularity represent important factors influencing evolutionary change. The mammalian cervical vertebral column is particularly interesting in regards to integration and modularity because it is highly constrained to seven elements, despite widely variable morphology. Previous research has found a common pattern of integration among quadrupedal mammals, but integration patterns also evolve in response to locomotor selective pressures like those associated with hominin bipedalism. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 123 publications
(332 reference statements)
1
21
1
Order By: Relevance
“…2), and considering that species represent feeding ecologies, we can deduce that the modular structure of the neck is not mainly linked to feeding ecology. Similar observations have been made in mammals, in which the patterns of modularity in the neck are highly conserved regardless of the species ecology (Arnold et al 2016(Arnold et al , 2017Villamil 2018), in contrast to those observed in the rest of the column (Jones et al 2018(Jones et al , 2019. To further extend these conclusions, they can be discussed in light of those reported for Felidae by Randau et al (2017), who concluded that "ecological factors influence the shape of the vertebral column heterogeneously and that distinct vertebral sections may be under different selection pressures".…”
Section: Modules (Ie Subsets Of Cvs)supporting
confidence: 64%
“…2), and considering that species represent feeding ecologies, we can deduce that the modular structure of the neck is not mainly linked to feeding ecology. Similar observations have been made in mammals, in which the patterns of modularity in the neck are highly conserved regardless of the species ecology (Arnold et al 2016(Arnold et al , 2017Villamil 2018), in contrast to those observed in the rest of the column (Jones et al 2018(Jones et al , 2019. To further extend these conclusions, they can be discussed in light of those reported for Felidae by Randau et al (2017), who concluded that "ecological factors influence the shape of the vertebral column heterogeneously and that distinct vertebral sections may be under different selection pressures".…”
Section: Modules (Ie Subsets Of Cvs)supporting
confidence: 64%
“…Murine vertebral outlines after Johnson and O'Higgins (1996) morphological modules of the neck. There are distinct shape changes between C2 and C3 as well as C5 and C6 (Johnson et al 1999;Buchholtz et al 2012;Arnold et al 2016;Böhmer 2017;Randau and Goswami 2017;Villamil 2018). C1 and C2 (atlas and axis), but also C6 and C7, each have unique morphologies, whereas C3 to C5 are more uniform.…”
Section: The Morphological Perspective: Bone Shape and Muscle Topologymentioning
confidence: 99%
“…Vertebral anatomy and its relationship to basicranial anatomy and posture in primates is the subject of some research (e.g. Russo & Kirk, ; Nalley & Grider‐Potter, ; Villamil, ), but our results demonstrate that its effect on cranial vault anatomy via the link with the nuchal musculature should be assessed as well.…”
Section: Discussionmentioning
confidence: 78%